2018
DOI: 10.1111/sms.13320
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better assessment of perceived social influence: The relative role of significant others on young athletes

Abstract: The purpose of this three‐study paper was to develop and validate the Perceived Social Influence in Sport Scale‐2 (PSISS‐2) that aimed to resolve the limitations of PSISS‐1 in assessing the relative social influence of significant others in youth sport. In Study 1, a pool of 60 items generated from revisiting a qualitative dataset about significant others of young athletes were examined by two expert panel reviews in terms of content validity, clarity, coverage, and age‐appropriateness, leading to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 81 publications
(262 reference statements)
7
37
0
1
Order By: Relevance
“…We applied the PSIS [22] to evaluate social influences of significant others in terms of positive reinforcement and punishment. The findings were supportive to the validity and the proposed predictive power of PSIS as reported in previous studies [21,22]. Positive reinforcement and punishment from social agents, in general, established positive and negative relationships with the commitment outcomes (i.e., competence, enjoyment, and effort) respectively, which was consis-effort (β PE = -0.18, p = < 0.01) in PE-group, but those in LE-group were not significant except the unexpected significant positive correlation with competence in LE-group (β LE = 0.27, p = < 0.01).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We applied the PSIS [22] to evaluate social influences of significant others in terms of positive reinforcement and punishment. The findings were supportive to the validity and the proposed predictive power of PSIS as reported in previous studies [21,22]. Positive reinforcement and punishment from social agents, in general, established positive and negative relationships with the commitment outcomes (i.e., competence, enjoyment, and effort) respectively, which was consis-effort (β PE = -0.18, p = < 0.01) in PE-group, but those in LE-group were not significant except the unexpected significant positive correlation with competence in LE-group (β LE = 0.27, p = < 0.01).…”
Section: Discussionsupporting
confidence: 91%
“…The findings supported the validity and predictive power of PSIS in the measurement of social influence from coach, teammates, and parents on children and adolescents [22]. Studies using PSIS found that positive reinforcement and punishment from significant others respectively formed positive and negative relationships with children's and adolescents' competence, enjoyment, and effort in sport, and moderate to large (25% to 57%) amount of variance of these outcome variables were explained [21,22].…”
Section: Social Influence Conceptualised As Positive Reinforcement Ansupporting
confidence: 65%
See 3 more Smart Citations